The first thing to do is to multiply the terms in the bracket. To do this, consider the rule that #a(b+c) = ab+ac#, and apply this rule to the terms we have here, #0.2(x-100)#, where #0.2=a#, #x=b# and #-100=c# After multiplying, the equation now looks like

#0.2x-2+0.6x=62#

Next we group all like terms together. As you can see, there are 2 terms of #x#, #0.2x# and #0.6x#. Simply add these two terms together to get

#0.8x-2=62#

The third step is to isolate the #x#-term, and to do this we add the opposite value of #-2# to both sides of the equation, which happens to be #2#. The equation now looks like this:

#0.8x=64#

The last step to do is divide both sides by #0.8#. Notice how the #x#-term #0.8x# is equal to #0.8 * x#. Since we want to isolate #x#, we use the reverse operator on the coefficent of #x#. The coeffiecent is 0.8, and the reverse operator is division, therefor we divide both sides of the equation by 0.8 to get

#x=80#

To prove this, substitute #x# for 80 in the original equation.

I hope that helped!